Handbook of Angioplasty and Stenting Procedures - Morgan, Robert A.; Walser, Eric.; SpringerLink (Online service) (London : Springer London, 2010)
The Techniques in Interventional Radiology series of handbooks describes in detail the various interventional radiology procedures and therapies that are in current practice. The series comprises four titles, which in turn cover procedures in angioplasty and stenting, transcatheter embolization and therapy, biopsy and drainage and ablation. Each book is laid out in bullet point format, so that the desired information can be located quickly and easily. Interventional radiologists at all stages, from trainees through to specialists, will find this book a valuable asset for their practice. The Handbook of Angioplasty and Stenting Procedures first discusses the basic tools and principles of these procedures, then moves onto describing each operation that can be performed using these techniques. Dr. Robert Morgan is Consultant Radiologist at St Georges$1 (BHospital, London, UK, and Dr. Eric Walser is Professor of Radiology at the Mayo Clinic in Florida, USA.s
Basic Tools Required to Perform Angioplasty and Stenting Procedures -- Arterial Pressure Measurements -- Drugs ? Pre-, Peri- and Post-intervention -- Arterial Access -- Venous Access -- General Principles of Angioplasty and Stenting -- Arterial Closure Devices -- Aortoiliac Angioplasty and Stenting -- Angioplasty and Stenting of the Superficial Femoral Artery and Popliteal Artery -- Subintimal Angioplasty -- Infrapopliteal Angioplasty and Stenting -- Renal Artery Angioplasty and Stenting -- Angioplasty/Stenting of Mesenteric Arteries -- Carotid Stenting and Angioplasty -- Intracranial and Vertebral Artery Angioplasty and Stenting -- Angioplasty/Stenting of the Subclavian and Axillary Arteries -- Stent-Grafting of the Thoracic Aorta -- Elective Endovascular Aneurysm Repair (EVAR) of Abdominal Aortic Aneurysms (AAA) -- Endovascular Management of Ruptured Abdominal Aortic Aneurysm -- Angioplasty/Stenting/Lysis/Thrombectomy of Hemodialysis Access -- Thrombolysis for Acute Lower Limb Ischemia -- Endovascular Treatment of Acute Stroke -- Venoplasty and Stenting -- Venous Thrombolysis and Thrombectomy for Deep Venous Thrombosis -- TIPS (Transjugular Intrahepatic Portosystemic Shunts).
Keywords: Medicine; Radiology, Medical; Interventional radiology; Medicine & Public Health; Imaging / Radiology; Interventional Radiology; Diagnostic Radiology; Neuroradiology